Appreciation and Judgement in Google Maps Restaurant Reviews in Marina Bay, Singapore - Melani Rahayu; Dedi Sulaeman; Ika Yatmikasari (Journal of Educational Studies, 2026)
Online restaurant reviews have become an important source of information in shaping customer perceptions and influencing dining decisions in digital platforms such as Google Maps. However, there is still limited linguistic analysis focusing on how evaluative meanings are constructed within these reviews, particularly in terms of Appreciation and Judgement. This study aims to analyze how Appreciation and Judgement are realized in Google Maps restaurant reviews in the Marina Bay Area, Singapore. This research employs a qualitative descriptive design using qualitative content analysis guided by Systemic Functional Linguistics, specifically the Appraisal Theory proposed by Martin and White (2005), to interpret evaluative meanings in naturally occurring restaurant reviews. The data consist of 16 selected restaurant reviews collected from Google Maps and analyzed based on attitudinal resources. The findings show that Appreciation is predominantly used to evaluate food quality, ambience, and overall dining experience, while Judgement is mainly directed toward staff behavior and service performance. Positive evaluations are more frequently expressed compared to negative ones, indicating generally favorable customer experiences. The findings contribute to the application of Appraisal Theory in digital tourism discourse by demonstrating how evaluative language systematically constructs customer perceptions of food, service, and dining experiences in location-specific restaurant reviews.